Diseño metodológico de una guía de acceso al comercio justo a través del análisis del caso UROCAL - Córdova Arias, Llily Mishell (2013)
Fair Trade was created as an initiative of international cooperation with countries of the North to small farmers in the south, with the aim of helping their communities to reduce poverty and exploitation through the creation of supportive relationships. But the global problem, as well as in Ecuador is that small producers are not part of a fair chain. In addition, they don´t know other commercial alternative. For this reason this research, aims to generate a methodological guide and knowledge for small producers to access into Fair Trade, prior to the presentation and analysis of a particular case of our country, which is located in the coastal zone of the provinces of Oro, Azuay and Guayas, known as UROCAL and the base group NUEVO MUNDO, who exports organic and Fair Trade bananas to markets like Germany, the U.S. and Canada.